Mari mengenal arkeologi Alkitab, D.L. Baker & John J. Bimson - Christianto, Victor (Jurnal Teologi Amreta (ISSN: 2599-3100), 2024)
Among the books on Biblical Archaeology, this book is especially useful for beginning readers. According to the authors of this book, the archaeology of the biblical lands, in the modern sense of a science, actually emerged only in the late 19th century.